Fatores associados ao aleitamento na primeira hora de vida e ao aleitamento materno exclusivo em maternidades públicas e privadas - Menezes, Angélica Tavares Santos de (2023)
Introduction: Breastfeeding (BF) in the intra-hospital environment plays an important role in supporting breastfeeding in the first hour of life (BF1h), in the continuity of exclusive breastfeeding up to six months and supplemented until two years of age, if necessary the support, promotion and protection of health professionals. Objective: To identify factors related to puerperal women and the practices of health professionals associated with BF1h and EBF in the immediate postpartum period, in public and private maternity hospitals. Methods: Cross-sectional study, carried out in public and private maternity hospitals in Uberlândia/MG. The sample consisted of puerperal women ≥ 18 years old, who were interviewed using a questionnaire containing questions about sociodemographic, gestational and postpartum information, about the practices of health professionals regarding BF management and about BF and formulas infants received in prenatal care and in the maternity. The outcomes were BF1h and EBF at the time of the interview. The association between predictors and outcomes was verified using multiple logistic regression models. A value of p<0.05 was considered statistically significant. All collected data were entered and analyzed using the Stata SE® version 15.0 statistical program. Results: The study showed that the frequency of BF1h was 53.7%, 62.8% in public maternity hospitals and 10.1% in private ones; and the frequency of EBF was 67%, with 72.2% in public and 52.3% in private. puerperal women attended at private maternity hospitals (OR=0.05; 95%CI=0.02;0.11) were less likely to have BF1h and mothers who received information about BF1h during prenatal care (OR=1.64; 95%CI=1.02;2.64) were more likely to have BF1h. For the EBF outcome, primiparous mothers (OR=0.58 CI95%=0.35;0.95) and those who received help to breastfeed (OR=0.47; CI95%=0.23;0.94) were less likely to breastfeed exclusively, while those who breastfed in the 1st hour of life (OR=1.84 CI95%=1.10;3.09) were more likely to breastfeed exclusively. Conclusion: The findings showed that puerperal women who were treated in private maternity hospitals, those who were primiparous and those who received assistance had the lowest chances of breastfeeding in maternity hospitals. Thus, it is necessary that professionals are qualified to assist these mothers in these moments of difficulty in the immediate postpartum period and, therefore, it is necessary to improve practices in hospital units, so that they become stronger as support networks in maternal and child care.